Development of cerebral infarction associated with methotrexate in systemic local scleroderma: a clinical case - Syrvatka, Roman; Trepet , Ganna (The Ukrainian Scientific Medical Youth Journal, 2025)
systemic sclerosis is a systemic disease affecting connective tissue and small blood vessels, with an incidence of 7 to 33 cases per 100,000 population in Europe. The drug of choice for the treatment of skin changes (systemic localized scleroderma) in systemic sclerosis is methotrexate. One of its side effects is hyperhomocysteinemia, which additionally damages the vessels and leads to atherosclerosis, thrombosis, and, accordingly, the development of cardiovascular and cerebrovascular diseases, in particular stroke. We aimed to investigate the pathogenetic component, the plan of diagnostic studies, and the tactics of treatment of a patient with ischemic cerebral infarction in the basin of the left middle cerebral artery in connection with the administration of methotrexate (10 mg once a week) in systemic localized scleroderma. Examination revealed mono paresis and hypoesthesia in the right upper limb and mild speech impairment; neuroimaging revealed signs of stenosis of the left middle cerebral artery and an ischemic focus of acute circulatory disturbance in the left frontal lobe, as well as hyperhomocysteinemia (17 μmol/l). The patient was admitted to the hospital due to symptoms that continued for more than 24 hours, prompting the initiation of the following therapeutic measures: antiplatelet therapy (acetylsalicylic acid 100 mg 1 time/day), normalization of blood pressure (perindopril arginine (5 mg)/indapamide (1.25 mg) 1 time/day), normalization of hypercholesterolemia and hyperlipoproteinemia (simvastatin 20 mg 1 time/day), normalization of homocysteine ​​levels (folic acid one capsule twice a day, B vitamin complex). The effectiveness of the treatment was confirmed by the absolute absence of neurological symptoms at the time of discharge.